2021
DOI: 10.1089/can.2020.0103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cannabidiol on the Long-Term Toxicity and Lifespan in the Preclinical Model Caenorhabditis elegans

Abstract: Introduction: Despite widespread use of cannabidiol (CBD), no lifelong toxicity study has been published to date. Caenorhabditis elegans is often used in preclinical lifelong toxicity studies, due to an estimated 60-80% of their genes having a human ortholog, and their short lifespan of *2-3 weeks. In this study, we examined both acute and long-term exposure studies of CBD at physiologically relevant concentrations. Materials and Methods: Acute toxicity was determined by treating day 1 adults with a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…elegans Aβ 1‐42 model although a recent pilot study showed some moderate increase of lifespan in wild‐type C . elegans after CBD administration 19 . These Aβ strains have been used for various behavioral assays and pharmacological screens, including the identification of novel compounds for treating neurodegeneration 20,21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…elegans Aβ 1‐42 model although a recent pilot study showed some moderate increase of lifespan in wild‐type C . elegans after CBD administration 19 . These Aβ strains have been used for various behavioral assays and pharmacological screens, including the identification of novel compounds for treating neurodegeneration 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…17,18 No study was carried out to examine if CBD can be used to extend lifespan and improve health span in C. elegans Aβ 1-42 model although a recent pilot study showed some moderate increase of lifespan in wild-type C. elegans after CBD administration. 19 These Aβ strains have been used for various behavioral assays and pharmacological screens, including the identification of novel compounds for treating neurodegeneration. 20,21 This study aimed to reveal the mechanism of action of CBD on Aβ-induced neurite degeneration, lifespan, and health span using in vitro and in vivo models of Aβ.…”
Section: Introductionmentioning
confidence: 99%
“…Although increasing evidence has shown the beneficial effects of CBD in different models of aging and age-associated disease [ 17 19 , 49 ], the molecular mechanism of how CBD affects neuronal aging remains elusive. In C. elegans , many physiological changes at the tissue, cellular, and molecular levels occur that are closely related to the effects of aging [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cannabidiol (CBD), a non-intoxicating cannabinoid from Cannabis sativa , exhibits a broad spectrum of beneficial pharmacological effects, including antipsychotic [ 13 ], pro-cognitive [ 14 ], anti-inflammatory [ 15 ], and antioxidant [ 16 ] properties. Recently, CBD treatment has been shown to increase lifespan and improve healthspan in different models, such as the nematode worm ( Caenorhabditis elegans ) [ 17 , 18 ] and zebrafish ( Danio rerio ) [ 19 ]. However, the exact mechanism through which CBD modulates lifespan is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, invertebrate models appear as a very promising alternative and have seen a gain in popularity in recent years [37][38][39][40][41]. The most used invertebrate models for toxicity trials among others are Artemia salina, Daphnia magna, Drosophila melanogaster, soil invertebrate Folsomia candida, the nematode Caenorhabditis elegans, and the Greater Wax Moth Galleria mellonella [38,[42][43][44]. Among all these in vivo insects' models, G. mellonella has several attractive benefits due to its practicality, in particular its low cost, ease of acquisition and handling (no specialist training or equipment is required), ability to survive at 37°C (unlike many other non-mammalian hosts), they are large enough (2 cm in length and weigh approximately 250 mg) for accurate dosing (unlike commonly used invertebrate models such as C. elegans and D. melanogaster) which make it possible to handle individual larvae and administer test compounds directly into each individual (which is not always possible with other smaller invertebrate models) and enhances the reproducibility of assays conducted using this model [37,38,45].…”
mentioning
confidence: 99%